Peran Gender sebagai Moderator dalam Hubungan Gaya Berpikir dan Efikasi Diri Pengambilan Keputusan Karier Siswa SMA - Dhaniar Gusna Fatimah; Wahyu Indianti (Fakultas Psikologi Universitas Tarumanagara, 2020)
In the career selection process of high school students, previous research has shown that career decision self-efficacy can be predicted from thinking styles. However, the self-efficacy of career decisions can differ between men and women. Therefore, the purpose of this study is to look at the role of gender as a moderator in the relationship of thinking styles with the self-efficacy of career decisions of high school students. The number of respondents in this study were 353 high school students. Furthermore, the variables were measured using a research questionnaire namely the Career Decision Self-Efficacy-Short Form (CDSE-SF) scale and Thinking Style Inventory-Revised II (TSI-R2) which had been adapted into Indonesian. Data were analyzed using PROCESS macros program from Hayes that contained in SPSS. The results show that gender can only moderate the relationship of type I thinking styles with career decision self-efficacy in senior high school students (b3 = -0,24, t=-2,51, p<0,05); while gender doesn’t become a moderator in the relationship of type II thinking styles with career decision self-efficacy of high school student (b3 = -0,12, t=-1,28, p>0,5). Limitation and suggestions for further research are discussed.